The impact of armed violence on students' educational attainment and the role of parents in resilience schooling and the education process - Assefa, Yalalem; Tilwani, Shouket Ahmad; Moges, Bekalu Tadesse; Shah, Mohd Asif (Heliyon, 2022)
The main purpose of this study was to explore the impact of the Tigray People Liberation Front (TPLF) armed violence on the attainment of students' education and the role of parents' involvement in the resiliency of schooling and the education process. In doing so, a convergent mixed-method research design was used. Accordingly, both qualitative and quantitative data were collected simultaneously, and the analysis was drawn upon both strands in search of patterns. Numbers of the study sample were n = 436 and the selection was bounded into three categories of subjects such as school principals (n = 22) for an interview, primary school teachers (n = 384) for a questionnaire and parents (n = 30) for focus group discussion selected through comprehensive, simple random and purposive sampling strategies respectively. Bothe thematic analysis and descriptive analysis (frequency and percentage) were used as data analysis strategies. As a result, the following findings were obtained: Destruction of school infrastructures generate substantial impediments to the supply of schooling. As a result, students' educational enrolment was lowered and students' dropout rate, out-of-school students' rate and related educational wastage increased. Therefore, it can be concluded that sound school administration and active participation of parents and the local community are urgently needed to continue the schooling and education process. Parents and the local community participated to reorganize school activities when the war affected areas were free from the war battle field. However, currently when this study is being investigated, they are looking back due to threats that the war will reawaken and devastate their efforts again. Educational attainment; Education wastage; Parents and community involvement; Resilience education; TPLF armed violence.